An argument for love in intercultural education for teacher education. Issue 6 (2nd November 2017) - Lanas, Maija
Abstract: This paper proposes rethinking intercultural education in teacher education, arguing that any discussion of student teachers' intercultural education should be connected more explicitly to a theoretical conceptualisation of love. The first part of the paper focuses on identifying discursive boundaries in engaging with intercultural education in teacher education. It is argued that if we are to develop intercultural education, we need to consciously move away from some discourses in teacher education, namely instrumentalism, performance orientation, emotionlessness and seeing the relationship between teacher and learner as static. The second half of the paper develops a theoretical alternative by engaging with the concept of love as a basis for intercultural education in pursuing an alternative to the instrumentalist, performance-based, non-emotional fixed-relationship ethos of intercultural education in teacher education.